The effect of addition selected amino acids in extender semen on quality and DNA stability of frozen-thawed Sumba Ongole bull spermatozoa - Syahruddin Said; Setiorini Setiorini; Amaitshaa Adella; Indah Sari; Nursafira Fathaniah; Tulus Maulana (Jurnal Ilmu Ternak dan Veteriner, 2019)
The objective of the current study was to asses the optimal concentration of glutamine, glycine and cysteine amino acids in tris-citric-acid-fructose egg yolks (TCFY) extender on quality of SO bull spermatozoa during freezing and thawing. In this study the DNA stability of frozen-thawed Sperm was also indentified. Three mature bulls maintained at PT. Karya Anugerah Rumpin, private cattle breeding company, West Java, Indonesia were used as semen donors. Semen was collected using artificial vagina and were evaluated prior to freezing. Semen was diluted with TCFY supplemented with different concentrations of amino acids (5, 15 and 25 mM glycine and glutamine, and 3, 5 and 7 mM cysteine) then processed for colling and freezing. Semen quality parameters (subjective motility, viability and membrane and DNA integrity). Data showed that in general the effect of addition of selected amino acids (glycine, glutamine and cysteine) into TCFY extenders on motility, viability and membrane integrity of SO spermatozoa after cooling were significantly different (p<0.05) higher than that of control. Addition of 15 mM glycine, 15 mM glutamine and 5 mM cysteine resulted in significant (p<0.05) increase post-thawing sperm motility and sperm viability as compared to that of control. Furthermore, when spermatozoa were stained with acridine orange after fixation with acetic alcohol, the DNA integrity of post-thawing spermatozoa showed that all spermatozoa were remain intact. In conclusion ,addition of 15 mM glycine, glutamine and 5 mM cysteine increase the cryoprotecting efficacy of bovine bull cryopreservation extender, and furthermore all DNA spermatozoa were remain intact.